Behaviour of sambar deer, (Rusa unicolor Kerr) at different captive facilities in Malaysia - Selvarajah, Kushaal (2022)
Sambar deer (Rusa unicolor) is listed as Vulnerable under the International Union for Conservation of Nature (IUCN) Red List. In Malaysia, its population is expected to be less than 700 left in the wild. Yet, this species is often seen only as a prey species to the Malayan tiger (Panthera tigris). The lack of published study in captivity and in the wild was a concern. The purpose of this study was to update the last study that was done in captivity on sambar deer and to better understand their behaviour on an individual and social behaviour in such settings. Direct and indirect observations were used for data collection purposes in all three sites. We had found there were differences in behaviour among the three captive sites namely Zoo Negara, Zoo Taiping and Sungkai Conservation Center that were researched. Our findings show that the tested factors such as temperature and sex do affect the behaviour of captive sambar on both observed social and individual behaviours. Behaviour such as foraging time was highly influenced by the feeding time at each captive site which also concurrently changed the behaviour and time spent on other behaviour such as rumination and sitting. Having a fixed feeding time may have altered or conditioned the captive population. A more sporadic or unscheduled feeding time may benefit and more importantly mimic their natural behaviour in the wild where foraging may be opportunistic. The study shows that there are several factors such as temperature that influence the behaviour and activity spent by sambar deer in captivity specific to the sites in this study. In addition, it was shown that temperature and time of day influenced the selective behaviour, both in observed individual and social behaviour. The notion of captive welfare is still a handle that is hard to grasp in the Malaysian context, hence the need for relevant stakeholders to take initiative to improve our animal’s welfare. In addition, more in depth and longer duration of behavioural observation needs to be carried out in order to understand sambar deer in captivity.